Synthesis and Correlation of Spectral Properties of Some Substituted 1,3-Diphenyl-2-Propen-1-Ones (Bangladesh Journal of Scientific and Industrial Research, 2007)
Seven arylideneacetophenones: 1-(4-chlorophenyl)-3-phenyl-2-propen-1-one (1a), 1-(4-nitrophenyl)-3-phenyl-2-propen-1-one (1b) , 1-(4-methoxyphenyl)-3-phenyl-2- propen-1-one (1c) , 1-(4-methylphenyl)-3-phenyl-2-propen-1-one (1d) , 1-(4- chlorophenyl)-3-(4-methoxyphenyl)-2-propen-1-one (1e) , 1-(4-methylphenyl)-3-(4- methoxyphenyl)-2-propen-1-one (1f) and 1,3-di(4-methoxyphenyl)-2-propen-1-one (1g) were synthesized from the corresponding substituted acetophenones and benzaldehydes in presence of sodium hydroxide in aqueous ethanol. The structures of the compounds 1a-g were confirmed by their UV, IR, 1H NMR, 13C NMR spectral data. Bangladesh J. Sci. Ind. Res. 42(1), 45-52, 2007